(untitled) (Fiep Bulletin - online, 2011)
Postural changes affect humans for thousands of years and, inadequate postures used to carry weights, such as a school bag, can lead to algesic processes. According to the OMS (2004) 85% of people have, already have or will have a back pain in their lives due to postural problems. The physiotherapist acts as a facilitator, searching for posture health through guidance, promotion and prevention of health; in order to improve the prognosis, or even avoid that these individuals come to the office or public service to seek treatment, reducing the socio-economic cost that these changes cause. AIM: Check the weight of school bag for students, as well as the presence of algesic processes due to their misuse, and the knowledge of students regarding their appropriate use. MATERIAL AND METHODS: This is a descriptive epidemiological study, transversal and quantitative, performed in a private institution in Osasco (S.P.), with a sample composed of fifty (n = 50) students attending the 1st to 8th semester of the Physiotherapy Course. The data collected was through a questionnaire with objective questions, used as variables. Compiled data were presented in tables and graphs of simple frequency expressed in numbers and percentages. The ethical and legal aspects were observed. RESULTS: We found that the criterion used on the purchase of school bag for 54% of respondents was the size of it. 50% believe that the backpack load with the two handles on the back is best suited to column, 56% using this type of bag, but only 54% carry this way, although they believe that the bag carried unilaterally is the least suitable for the column (12%), 42% carry this way; 76% unaware of the existence of the "recommended weight” or backpack Law No. 2772/97 and 90% carry a backpack weighing more than that recommended by OMS and the backpack Law. All of these factors may be associated with algesic processes found in the students (50% lumbar, 42% shoulder, 22% cervical). CONCLUSION: The results suggest lack of knowledge of respondents regarding the proper use of various types of backpacks available, and the problems caused to themselves by their misuse. These data refer to the need for better education in the training of future health professionals, for better training of activity in promotion and prevention of posture health.